ANALISIS KERUSAKAN MESIN FRAIS FEHLMANN PICOMAX 20 MENGGUNAKAN METODE ROOT CAUSE ANALYSIS DI POLMAN BABEL - Sitinjak, Harpois S; Pratama, Adrian Deka; Masdani, Masdani; Napitupulu, Robert (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2025)
This study aims to identify the root cause of damage to the vertical head motion mechanism of the Fehlmann Picomax 20 milling machine at the Bangka Belitung State Polytechnic of Manufacturing using the Root Cause Analysis (RCA) method. This descriptive research with a qualitative approach involves collecting primary data through direct observation and interviews with machine operators and technicians. Secondary data is obtained from the machine's repair history and related literature. Analysis using the 5W+1H and Fishbone Diagram methods reveals that the machine damage is caused by irregular maintenance, the use of inappropriate lubricating oil, the use of low-quality components, and untrained operators. The recommendations for improvement include operator training, regular repairs, the use of appropriate materials, and environmental maintenance. This research successfully achieves its main objective, which is to systematically identify and analyze the root cause of machine damage and provide improvement recommendations to prevent recurring damage.